Interventions to support effective communication between maternity care staff and women in labour: A mixed-methods systematic review. (April 2018) - Chang, Yan-Shing; Coxon, Kirstie; Portela, Anayda Gerarda; Furuta, Marie; Bick, Debra
Abstract: Objectives: the objectives of this review were (1) to assess whether interventions to support effective communication between maternity care staff and healthy women in labour with a term pregnancy could improve birth outcomes and experiences of care; and (2) to synthesize information related to the feasibility of implementation and resources required. Design: a mixed-methods systematic review. Setting and participants: studies which reported on interventions aimed at improving communication between maternity care staff and healthy women during normal labour and birth, with no apparent medical or obstetric complications, and their family members were included. 'Maternity care staff' included medical doctors (e.g. obstetricians, anaesthetists, physicians, family doctors, paediatricians), midwives, nurses and other skilled birth attendants providing labour, birth and immediate postnatal care. Studies from all birth settings (any country, any facility including home birth, any resource level) were included. Findings: two papers met the inclusion criteria. One was a step wedge randomised controlled trial conducted in Syria, and the other a sub-analysis of a randomised controlled trial from the United Kingdom. Both studies aimed to assess effects of communication training for maternity care staff on women's experiences of labour care. The study from Syria reported that a communication skills training intervention for resident doctors was not associated with higher satisfaction reported by women. In the UK study, patient-actors' (experienced midwives) perceptions of safety and communication significantly improved for postpartum haemorrhage scenarios after training with patient-actors in local hospitals, compared with training using manikins in simulation centres, but no differences were identified for other scenarios. Both studies had methodological limitations. Key conclusions and implications for practice: the review identified a lack of evidence on impact of interventions to support effective communication between maternity care staff and healthy women during labour and birth. Very low quality evidence was found on effectiveness of communication training of maternity care staff. Robust studies which are able to identify characteristics of interventions to support effective communication in maternity care are urgently needed. Consideration also needs to be given to how organisations prepare, monitor and sustain interventions to support effective communication, which reflect outcomes of priority for women, local culture and context of labour and birth care. Highlights: The review found only two studies on interventions for effective communication. Neither study considered clinical outcomes of interventions. Satisfaction with care was considered in both studies. Neither study presented qualitative data on women's and clinicians' experiences. Current evidence is inadequate to inform content of training or practice.